Culture Shock dan Strategi Penyesuaian Diri Mahasiswa Perantau - Arifiati, Retna febri Arifiati; Wahyuni, Endang Sri (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Migrant students often experience culture shock when entering a new environment. This occurs because of the reaction in finding cultural differences that have been adhered to. The effect can potentially experience difficulties in adjusting such as lack of interaction, having negative prejudices, and sometimes causing stress. Culture shock can be overcome if a person is able to adapt and adjust to the culture where the individual is. Objectives: The purpose of this study was to determine whether there is a relationship between culture shock and the adjustment of migrant students in the Occupational Therapy Department of the Ministry of Health Polytechnic of Surakarta Class of 2024. Methods: This type of research is cross-sectional. The sample selection technique used purposive sampling where there are special criteria in selecting the sample, namely Occupational Therapy Department students class of 2024 who come from outside Central Java. Furthermore, students were given a google form link containing a culture shock questionnaire consisting of 54 items and an adjustment questionnaire consisting of 30 items. The total number of respondents obtained was 78 students. Hypothesis testing used product moment correlation. Results: Showed that respondents were predominantly female, namely 66 respondents (84.6%), coming from East Java, namely 32 respondents (41%). Based on the product moment regression analysis, the value of r = -0.643 was obtained, which means there is a significant negative relationship between the culture shock variable and the student's self-adjustment variable with a p value = 0.000 (p <0.05) with an effective contribution of 41.34% and 58.65% from other factors. Conclusion: There is a negative relationship between culture shock and the self-adjustment of migrant students, where the higher the level of culture shock of migrant students, the lower the level of their adjustment and the lower the level of culture shock of migrant students, the higher the level of their adjustment. Keywords: Culture Shock, Adjustment, Out-of-Town Students, New Students